Green initiative to reduce carbon emission for aeroplanes using Malaysia Airlines Berhad as a case study / Indera Shah Reza Govinathan - Indera Shah Reza, Govinathan (2018)
A case study was carried out in Malaysia Airlines Berhad (MAB) to evaluate the green initiatives carried out to reduce CO₂ emission. The reduction in fuel consumption relatively reduces the CO₂ emission thus having mutual benefits both financially and environmentally. The four-pillar strategies comprising of technological improvement, operational efficiencies, infrastructure development and market-based measures developed by the International Association of Air Travel (IATA) are used as a basis for the evaluation on the initiatives carried out by MAB in reducing their CO₂ emission and fuel consumption. Many initiatives carried out by the organization has resulted in positive results. The Boeing 737 fleet which operates 80% of Malaysia Airlines routes are evaluated individually. Additional strategies that could be implemented further concluded that a further 55,626 tonnes of fuel consumption and 175,221 tonnes of CO₂ reduction could be further achieved. These strategies adopted by the aviation industry in mitigating climate change could also be extended to other industry in Malaysia such as the ground transportation. Some of the strategies are worth exploring and the role of the stakeholders in taking the necessary steps by adopting similar measure like in the aviation industry is of prime importance. Malaysia being the home of three growing international airlines and with one of the highest number of private vehicle owners in this region needs to fast track its vision of becoming a developed country by 2020. Key word: Carbon emission, fuel consumption, aviation